Perlindungan Hak Masyarakat Adat terhadap Tanah Ulayat Berdasarkan UU Pokok Agraria - Lalu M. Hasan (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2024)
This study aims to: (1) analyze the legal provisions for indigenous peoples and customary land in the Basic Agrarian Law (Law No. 5 of 1960); (2) assess the effectiveness of legal protection provided for the rights of indigenous peoples; and (3) analyze the legal mechanisms that ensure customary land remains under the control of indigenous peoples fairly and in accordance with the principles of justice. This study is a normative legal study with a legislative approach, a conceptual approach, a historical approach, and a philosophical approach. The legal materials used include primary legal materials, secondary legal materials, and tertiary legal materials. The analysis is carried out through grammatical, systematic, and teleological interpretations, as well as the application of legal theory by adhering to legal principles. The results of the study indicate that 1) formal recognition of customary rights through the Basic Agrarian Law and electronic documents in the ITE Law provide a valid legal basis, 2) administrative procedures and integration with customary law guarantee legal certainty and protection of rights, and 3) consistent and transparent legal mechanisms ensure that indigenous peoples' rights to customary land are maintained fairly and equitably